Impact of Brand Image and Brand Loyalty in Measuring Brand Equity of Islami Bank Bangladesh Ltd. - Fatema, Mohsina; Azad, Md. Abul Kalam; Masum, Abdul Kadar Mohammad (Asian Business Review, 2013)
This paper aims at investigating the interrelation between brand image and brand loyalty in case of measuring brand equity of Islami Bank Bangladesh Ltd. Brand Image (BI) and Brand Loyalty (BL) have been considered as the most attributing features of Brand Equity. Handful of researches have resulted these two as primary factor (Latent Variable) of Brand Equity. With this association, this study is designed at conducting research for explaining intermediating role of BI and BL over Brand equity of Islami Bank Bangladesh Limited (IBBL) using Structured Equation Modeling (SEM). Specifically, to analyze the impact of observed variables over un-observed variable e.g. BI and BL we have used Confirmatory Factor Analysis. Only primary data was used for the study which was collected through structured questionnaire from a total number of 399 customers’ located in 43 branches of IBBL within Dhaka city. Simple Random Selection (SRS) was followed for sampling design. Findings of the study show that a positive correlation exists between BI and BL for IBBL. Moreover, strong influence of Brand Loyalty over Brand Equity was found that of Brand Image in case of IBBL. The model fit of the study strongly signify the result as successful estimate of the model.